Stimuli-Responsive Polymers for Transdermal, Transmucosal and Ocular Drug Delivery - Dmitriy Berillo; Zharylkasyn Zharkinbekov; Yevgeniy Kim; Kamila Raziyeva; Kamila Temirkhanova; Arman Saparov (MDPI AG, 2021)
Despite their conventional and widespread use, oral and intravenous routes of drug administration face several limitations. In particular, orally administered drugs undergo enzymatic degradation in the gastrointestinal tract and first-pass metabolism in the liver, which tend to decrease their bioavailability. Intravenous infusions of medications are invasive, painful and stressful for patients and carry the risk of infections, tissue damage and other adverse reactions. In order to account for these disadvantages, alternative routes of drug delivery, such as transdermal, nasal, oromucosal, ocular and others, have been considered. Moreover, drug formulations have been modified in order to improve their storage stability, solubility, absorption and safety. Recently, stimuli-responsive polymers have been shown to achieve controlled release and enhance the bioavailability of multiple drugs. In this review, we discuss the most up-to-date use of stimuli-responsive materials in order to optimize the delivery of medications that are unstable to pH or undergo primary metabolism via transdermal, nasal, oromucosal and ocular routes. Release kinetics, diffusion parameters and permeation rate of the drug via the mucosa or skin are discussed as well.